Hormonal protocols for artificial insemination at fixed time in crossbred female buffaloes in different reproductive categories and seasons of ovarian activity in Cuba - Gallego, Carlos (Cuban Journal of Agricultural Science, 2017)
From a herd of 348 crossbred river female buffaloes (Bubalus bubalis), 82 and 120 nulliparous females were used from the total during the season of highest and lowest ovarian activity, respectively and 146 multiparous during the season of highest reproductive activity for assessing hormonal protocols that improvethe reproductive efficiency for the Artificial Insemination at a Fixed Time (AIFT) in different seasons of the year and reproductive categories. Hormonal protocols for the AIFT using CG and CE2 had better efficiency in nulliparous buffaloes during the season of lowest ovarian activity, while in the stage of highest reproductive activity treatments combining PGF2α and GnRH were the most efficient in the nulliparous and in multiparous in a period longer than 45 days post-calving. For the first time information is offered in Cuba of buffalo females on the performance and reproductive efficiency with the use of hormonal protocols synchronizing the follicular growth, the luteous phase and the ovulation of AIFT in nulliparous and multiparous and seasons of higher and lower ovarian activity under field conditions which contributes in an accelerated way to the reproductive and genetic development of the Cuban herds and of other regions of the Caribbean and Central America.